IMPACT OF ZINC SUPPLEMENTATION ON DURATION OF HOSPITALIZATION IN CHILDREN WITH PNEUMONIA - ASHRAF, F; BABAR, H; AHMED, S; SHAHWANI, NK; RABNAWAZ, K; ANIS, M (Biological and Clinical Sciences Research Journal, 2024)
Zinc supplementation is known to reduce pneumonia incidence among infants; however, its role in improving treatment outcomes for pneumonia in hospitalized children remains inconclusive. Objective: This study investigates the effect of zinc supplementation on the duration of hospitalization and symptom severity in pediatric patients diagnosed with pneumonia. Methods: A randomized controlled trial was conducted at the Balochistan Institute of Child Health Service, Quetta, Pakistan. A total of 100 children diagnosed with pneumonia were enrolled and randomized into two groups: a zinc supplementation group and a control group. Data were analyzed using SPSS software, employing regression and correlation analyses to assess the impact of zinc on hospitalization duration and symptom severity. Results: Statistical analysis revealed no significant difference in hospitalization duration or symptom severity between the zinc-supplemented group and the control group (p-values of 0.741 and 0.402, respectively). The findings suggest that zinc supplementation does not significantly alter treatment outcomes in terms of reducing hospital stay or symptom intensity for children with pneumonia. Conclusion: While zinc supplementation is recognized for its role in pneumonia prevention, this study does not support its efficacy in reducing hospitalization duration or symptom severity for children already diagnosed with pneumonia. Further research is recommended to explore alternative therapeutic strategies for enhancing recovery outcomes in pediatric pneumonia cases.